Impact of Transformational Leadership and Job Resources on Turnover Intention Mediated by Work Engagement (Case Study BUMN Banking Employees) - Sapri, Sapri; Warsindah, Lucy (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Turnover Intention is a problem that is always faced by every company and becomes a problem that is never resolved—the need for good and proper control so that the company's performance is maintained. The purpose of this study was to determine the effect of transformational leadership and job resources on turnover intention mediated by work engagement in employees who work in state-owned banks. Quantitative research was used with sampling techniques namely purposive sampling. The number of samples used was 205 state-owned banking employees. The data analysis technique was used the SEM-PLS analysis method. Based on the results it was found that transformational leadership and job resources affect work engagement, but do not affect turnover intention. Work engagement can mediate the impact between transformational leadership and turnover intention. Likewise, work engagement can mediate the impact between job resources and turnover intention.